The Synthesis and Characterisation of Ru(III)-Substituted Keggin-Type Phosphomolybdates - Max Papajewski; Jan-Christian Raabe; Hamid Anwari; Dorothea Voß; Jakob Albert; Maximilian J. Poller (Inorganics, 2025)
Polyoxometalates are a promising family of compounds for the development of new catalyst materials, although up to now they have mainly been applied in acid catalysis and oxidative processes. In this study, we present the synthesis and characterisation of two new Keggin-type phosphomolybdates, H6[PRuMo11O40] and H9[PRu2Mo10O40]. The successful synthesis was confirmed with ICP-OES (elemental composition) and infrared spectroscopy (structure). Furthermore, the molecular structure of H6[PRuMo11O40] was determined by electron diffraction. The new compounds were comprehensively characterised using 31P-NMR spectroscopy, UV-Vis spectroscopy, and electrochemical methods. Square-Wave-Voltammetry revealed an additional RedOx peak for the Ru-substituted POMs compared to the unsubstituted phosphomolybdate at around 825 mV. In a test reaction, the new compounds showed promising catalytic activity for the hydrogenation of lactic acid.